ESF: an efficient security framework for wireless sensor network. (1st January 2013) - Tripathy, Somanath
A wireless sensor network (WSN) consists of a large number of resource constrained sensor nodes, usually deployed in hostile environments, where they face a variety of malicious attacks. To address the security vulnerabilities in WSN, this paper proposes an efficient security framework (ESF), which comprises of two security building blocks. The first one security building block is to establish key between the sending and receiving nodes while other component provides confidentiality and integrity of data. Owing to the limited resources available with the sensor nodes, ESF avoids intensive computations like public key cryptography and encryption mechanisms. Analysis of ESF shows that the framework provides a secure environment and resistant against the wireless threats using simple bit-wise operations and cryptographic hash functions.